2019
DOI: 10.3390/ijms20122915
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Induces the Risk of Metabolic Bone Diseases: Transforming Growth Factor Beta Signaling Impairment via Dysfunctional Primary Cilia Affects Migration, Proliferation, and Differentiation of Human Mesenchymal Stem Cells

Abstract: It is well established that smoking has detrimental effects on bone integrity and is a preventable risk factor for metabolic bone disorders. Following orthopedic surgeries, smokers frequently show delayed fracture healing associated with many complications, which results in prolonged hospital stays. One crucial factor responsible for fracture repair is the recruitment and differentiation of mesenchymal stem cells (MSCs) at early stages, a mechanism mediated by transforming growth factor β (TGF-β). Although it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 74 publications
1
52
1
Order By: Relevance
“…Aspera-Werz et al reported that although nicotine and cotinine did not directly induce ROS, they impaired the anti-oxidative defense mechanisms within mesenchymal stem cells by inhibiting anti-oxidative enzyme activity [44]. In our study, ROS production was generated significantly when chondrocytes were exposed to 10% CSE, which is in line with smoking approximately 20 cigarettes (1 pack) a day [40]. As chondrocytes are normally in a quiescent condition and only proliferate once activated, the survival and death of chondrocytes are vital for the preservation of articular cartilage [14].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Aspera-Werz et al reported that although nicotine and cotinine did not directly induce ROS, they impaired the anti-oxidative defense mechanisms within mesenchymal stem cells by inhibiting anti-oxidative enzyme activity [44]. In our study, ROS production was generated significantly when chondrocytes were exposed to 10% CSE, which is in line with smoking approximately 20 cigarettes (1 pack) a day [40]. As chondrocytes are normally in a quiescent condition and only proliferate once activated, the survival and death of chondrocytes are vital for the preservation of articular cartilage [14].…”
Section: Discussionsupporting
confidence: 85%
“…Toxins contained in cigarettes have been shown to induce oxidative stress [2], inflammatory responses [38], or hypoxia [39], which all can damage cartilage. Recently, we reported that CSE negatively affects the migration, proliferation, and chondrogenic differentiation of mesenchymal stem cells through impairing the transforming growth factor-β (TGF-β) signaling [40]. However, the effects of cigarette smoke on primary human chondrocytes remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclei were stained with Hoechst 33342 (1:1000). Images were taken with an epifluorescence microscope (EVOS FL, life technologies, Darmstadt, Germany), and primary cilia length was analyzed using the ImageJ software (Version 1.5, NIH, Bethesda, MD, United States) (line tool) based on the maximum intensity projection method[ 39 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…Alkaline phosphatase (ALP) activity was significantly higher in co-cultures with SaOS-2 cells, which have a very high basal ALP activity [205], than in co-cultures with SCP-1 cells, which normally show an increase in ALP activity with differentiation [206] (Figure 5C). Consequently, after 14 days of culture formation of mineralized matrix was also higher in co-cultures with SaOS-2 cells than in co-cultures with SCP-1 cells ( Figure 5D).…”
Section: Choice Of Suitable Osteoclast Precursor Cellsmentioning
confidence: 99%